A new species of Rhaebo (Anura: Bufonidae) from the Cordillera Occidental of Colombia - Mueses-Cisneros, Jonh Jairo (Zootaxa, 2007)
A new species of the genus Rhaebo is described from the Cordillera Occidental of Colombia. Rhaebo lynchi sp. nov. differs from all others congeners in having a row of very prominent tarsal tubercles on the outer edge, a row of very prominent ulnar tubercles, short limbs, and smaller size in adult. R. lynchi is currently the smallest known Rhaebo.